A Summer of Mass Murder 1941 Rehearsal for the Hungarian Holocaust - Eisen, George (Purdue University Press, 2022)
Most accounts of the Holocaust focus on trainloads of prisoners speeding toward Auschwitz, with its chimneys belching smoke and flames, in the summer of 1944. This book provides a hitherto untold chapter of the Holocaust by exploring a prequel to the gas chambers: the face-to-face mass murder of Jews in Galicia by bullets. The summer of 1941 ushered in a chain of events that had no precedent in the rapidly unfolding history of World War II and the Holocaust. In six weeks, more than twenty thousand Hungarian Jews were forcefully deported to Galicia and summarily executed. In exploring the fate of these Hungarian Jews and their local coreligionists, A Summer of Mass Murder transcends conventional history by introducing a multitude of layers of politics, culture, and, above all, psychology?for both the victims and the executioners. The narrative presents an uncharted territory in Holocaust scholarship with extensive archival research, interviews, and corresponding literature across countries and languages, incorporating many previously unexplored documents and testimonies. Eisen reflects upon the voices of the victims, the images of the perpetrators, whose motivation for murder remains inexplicable. In addition, the author incorporates the long-forgotten testimonies of bystander contemporaries, who unwittingly became part of the unfolding nightmare and recorded the horror in simple words. This book also serves as a personal journey of discovery. Among the twenty thousand people killed was the tale of two brothers, the author?s uncles. In retracing their final fate and how they were swept up in the looming genocide, A Summer of Mass Murder also gives voice to their story.